Reproductive biology of the swimming crab achelous spinimanus (Decapoda, portunoidea): A potential fishing resource - Sousa, Aline N. [UNESP]; Bernardes, Veronica P. [UNESP]; Bernardo, Camila H. [UNESP]; Taddei, Fabiano G. [UNESP]; Teixeira, Gustavo M. [UNESP]; Costa, Rogério C. [UNESP]; Fransozo, Adilson [UNESP] (FapUNIFESP (SciELO), 2020)
This study describes the reproductive and recruitment patterns of the swimming crab Achelous spinimanus (Latreille, 1819) in the Ubatuba region of the northern coast of São Paulo, Brazil. Crabs were captured monthly from January 1998 to December 1999 in 18 sites located in three bays (Ubatumirim, Ubatuba, and Mar Virado), using a commercial fishing boat. In each sampling area, bottom temperature, salinity, and organic matter content were recorded. A total of 1,911 individuals were captured: 350 adult males, 475 non-ovigerous adult females, 584 adult ovigerous females, and 502 immature individuals. Reproductive females were more abundant in deeper areas; this migration might be a strategy to improve larval dispersion and survival. Ovigerous females were found year-round, indicating a continuous reproduction, and their abundance was positively correlated with temperature. During the 2-year survey, crabs with all gonadal development stages were found. We can infer that this region provides suitable resources for the development of A. spinimanus.
Biologia reprodutiva do siri achelous spinimanus (Decapoda, portunoidea): um recurso pesqueiro em potencial.
Keywords: Fishing; Organic matter; Recruitment; Temperature; Ubatuba